Detection of Echovirus-18 in Children Suspected With SARS-CoV-2 Infection With Multisystem Inflammatory Syndrome: A Case Report From India - Lavania, Mallika; Viswanathan, Rajlakshmi; Bhardwaj, Sumit Dutt; Oswal, Jitendra S.; Chavan, Nutan; Shinde, Manohar; Katendra, Savita (Frontiers in Public Health, 2022)
There have been several reports across the globe regarding the presentation of a severe multi-system hyperinflammatory syndrome, resembling Kawasaki disease (KD), in the pediatric population during the SARS-CoV-2 pandemic. The exact pathophysiology is still unclear; however, children typically demonstrate multi-organ dysfunction and less respiratory system involvement compared to adults. The limited literature is available at present for the identification and management of such patients. In this study, we investigated four cases in children ages 11–15 years that fulfilled the case definition for the pediatric multi-system inflammatory syndrome. All were found negative for SARS-CoV-2 from oropharyngeal swabs and stool. As they were having symptoms of diarrhea, tests for bacterial and enteric viral infections were performed after SARS-CoV-2 testing. Molecular analysis revealed that all the children were infected with enterovirus (Echovirus-18). Early and exact diagnosis is vital for timely, effective, and potentially life-saving management of such cases.